Benchmarking risk management practice within the water utility sector - MacGillivray, Brian H. (Cranfield University, 2006)
Explicit approaches to risk analysis within the water utility sector, traditionally applied to occupational health and safety and public health protection, are now seeing broader application in contexts including corporate level decision making, asset management, watershed protection and network reliability. Our research suggested that neither the development of novel risk analysis techniques nor the refinement of existing ones was of paramount importance in improving the capabilities of water utilities to manage risk. It was thought that a more fruitful approach would be to focus on the implementation of risk management rather than the techniques employed per se. Thus, we developed a prescriptive capability maturity model for benchmarking the maturity of implementation of water utility risk management practice, and applied it to the sector via case study and benchmarking survey. We observed risk management practices ranging from the application of hazard and operability studies, to the use of scenario planning in guiding organisational restructuring programmes. We observed methods for their institutionalisation, including the use of initiation criteria for applying risk analysis techniques; the adoption of formalised procedures to guide their application; and auditing and peer reviews to ensure procedural compliance and provide quality assurance. We then built upon this research to develop a descriptive1 capability maturity model of utility risk analysis and risk based decision making practice, and described its case study application. The contribution to knowledge of this stage of the research was three-fold, we: synthesized empirical observations with behavioral and normative theories to codify the processes of risk analysis and risk based decision making; placed these processes within a maturity framework which distinguishes their relative maturity of implementation from ad hoc to adaptive; and provided a comparative analysis of risk analysis and risk based decision making practices, and their maturity of implementation, across a range of utility functions. The research provides utility managers, technical staff, project managers and chief finance officers with a practical and systematic understanding of how to implement and improve risk management, and offers preliminary guidance to regulators concerning how improved water utility governance can be made real.